PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 013 POLAK PISANG I KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Eli Sarkis; Eddy Noviana; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improved learning outcomes IPA fourth grade students of SD Negeri 013 Polak Pisang I Sub Kelayang Indragiri Hulu by using model study of Quantum Teaching. Thus, the hypothesis in this study is that if implemented Quantum Teaching learning model can improve student learning outcomes IPA. This research is a classroom action research (Classroom Actions Research). The subject is the fourth grade students of SD Negeri 013 Polak Bananas I, which totaled 20 students consisting of 7 male students and 13 female students. From the research data can be known from the teacher's activities during the learning process using the learning model application Quantum Teaching in the first cycle an average of 79.16% success with both categories. In the second cycle the average success for the activities of teachers in the second cycle of 89.58% with a good category. Activities of students during the learning process using the learning model application Quantum Teaching batting average of 66.66% first cycle with enough category. In the second cycle success rate reached 91.66% with a good category. Thus, it can improve student learning outcomes IPA from basic score (64.75) to UH I (68.25) have increased (5.40%). Basic score (64.75) to UH II (85.5) has increased (25,27%). Of the 20 students, on a base score only 8 (40%) of students who pass. In the first cycle there were 13 (65%) of students who pass. Cycle II students who complete a total of 20 (100%) of students. It can be concluded that the application of the model Quantum Teaching can improve learning outcomes IPA fourth grade students of SDN 013 Polak Pisang.Keywords: Learning Model Quantum Teaching and Learning Outcomes IPA